The influence of physical activity for the prevention and treatment of osteoporosis: integrative review (Research, Society and Development, 2021)
Objective: This study aimed to verify the influence of physical activity on the prevention and treatment of osteoporosis. Methods: Integrative literature review, carried out through a search in the Pubmed and Scielo databases using the crossings of the descriptors in English "Osteoporosis", "Prevention", "Physical exercise", using the Boolean operator "and". To evaluate the research problem and its stratification, the PVOstrategy was used. For the construction of this article, the following question was applied: How does physical activity influence the prevention and treatment of osteoporosis? For the inclusion criteria, articles written in English and Portuguese were included and published between the years 2015 to 2020. After a selective reading of the texts, 19 articles were selected that responded to the purpose of the study. Results and Discussion: Exercise can improve or maintain bone mass at all ages and studies show that exercise can improve physical function, quality of life, pain and vitality in osteoporotic and osteopenic postmenopausal women. These specific exercises must be dynamic, exceed a limit of strain intensity and frequency, impose an unusual load pattern on the bones, and be supported by unlimited nutritious energy. Conclusion: Exercise can improve or maintain bone mass at all ages and can also improve physical function, quality of life, pain and vitality. Exercises must be dynamic, exceed a limit of strain intensity and frequency, impose an unusual load pattern on the bones, and be supported by unlimited nutritious energy.